Perceived Stress, Its Physiological Correlates, and Quality of Life in Patients With Irritable Bowel Syndrome. Issue 3 (May 2018) - Weaver, Kristen R.; Melkus, Gail D'Eramo; Fletcher, Jason; Henderson, Wendy A.
Irritable bowel syndrome (IBS) is a chronic, common disorder of the gastrointestinal tract associated with high psychological comorbidity and diminished quality of life. Patients with IBS display a heightened sensitivity to stress, although the literature is inconsistent as to whether they have a dysregulated stress response. The purpose of the present investigation, a substudy of a larger research effort, was to examine physiological correlates of perceived stress in patients with IBS (cortisol and adrenocorticotropic hormone) and to explore associations between perceived stress and quality of life. A total of 101 participants (35 with IBS [predominant subtypes IBS-constipation and IBS-diarrhea] and 66 healthy controls [HCs]) completed self-report inventories regarding perceived stress and quality of life, and fasting peripheral blood was drawn. Participants with IBS did not differ from the HC in demographic or physiological measures but did differ in psychological measures, reporting significantly higher levels of perceived stress and lower levels of quality of life. Perceived stress and quality of life were not significantly associated in IBS participants. However, differential findings of the stress response were found within IBS participants by sex, race, and subtype. These findings illustrate the heterogeneity of the IBS patient population, underscore the necessity of evaluating larger sample sizes and increasing the diversity of such samples to include males and ethnic minorities, and demonstrate the importance of taking an individualized approach to evaluation and treatment in the IBS patient population.